2004
DOI: 10.1161/01.cir.0000146890.93172.6c
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell–Derived Factor-1 and CXCR4 Interaction Is Critical for Development of Transplant Arteriosclerosis

Abstract: Background-Posttransplant chronic allograft deterioration associated with development of transplant arteriosclerosis (TA) remains an unresolved problem. Recent studies suggest that the smooth muscle cells (SMCs) constituting the neointima are derived from recipient hematopoietic stem cells (HSCs). However, the underlying mechanisms of the process are not yet fully elucidated. Methods and Results-We examined the genes expressed in allografts at different stages of TA development using a mice aortic transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…Thus, injection of SDF-1␣-overexpressing MSCs in the ischemic myocardium provides a novel strategy whereby the recruitment of CXCR4-positive progenitor cells may be enhanced so as to facilitate repair of the injured myocardium. However, long-term overexpression of SDF-1␣ has been reported to cause chronic allograft deterioration associated with the development of transplant arteriosclerosis (23). Accordingly, further study on the duality of SDF-1␣ action is clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, injection of SDF-1␣-overexpressing MSCs in the ischemic myocardium provides a novel strategy whereby the recruitment of CXCR4-positive progenitor cells may be enhanced so as to facilitate repair of the injured myocardium. However, long-term overexpression of SDF-1␣ has been reported to cause chronic allograft deterioration associated with the development of transplant arteriosclerosis (23). Accordingly, further study on the duality of SDF-1␣ action is clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to representing hematopoietic stem cells, c-Kit + /Sca-1 + /Lin-1 − (KSL) cells in circulating blood have also been considered vascular progenitor cells derived from bone marrow [21,22,24]. CD34 + cells (hematopoietic progenitors) are population of cells enriched with EPCs [4,18], and CD34 + /Flk-1 + cells participate in therapeutic neovascularization [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been suggested that cells expressing CD34 + /Flk-1 + participate in therapeutic neovascularization [20]. It is also important to note that, hematopoietic stem cells, characterized by co-expression of stem cell antigen-1 (Sca-1) and receptor for stem cell factor, c-kit [21,22,24], posses the ability to differentiate into nonhematopoietic tissues, including cardiac myocytes [19].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 An upregulation of Cxcl12 has been observed in transplant arteriopathy or in hypoxia, and blocking Cxcl12 or Cxcr4 reduced neointima formation and SMC progenitor recruitment in transplant arteriosclerosis or during neovascularization of ischemic tissues. 10,11,14 The expression of CXCL12 is also detectable in primary atherosclerotic plaques, 15 and reduced CXCL12 plasma levels have been associated with unstable coronary artery disease, suggesting antiinflammatory or plaque-stabilizing properties of CXCL12. 16 Owing to the embryonic lethality after genetic deletion, a role of Cxcl12/Cxcr4 in the development, stability, and cellular homeostasis of primary atherosclerosis has not yet been studied in vivo.…”
mentioning
confidence: 99%